Central Business District Corporate Sports Center - Liganor, Manuel Alejandro G.; Meonada, Jose Mari E. (Quezon City College of Architecture, University of the Philippines Diliman, 2016)
Health is essential to the workforce especially in a central business district. We fail to realize the value of our health until a person's body becomes ill dues to the different stresses it undergoes day in and out. This thesis looks into the possibility of a change to a healthier lifestyle through an injection of a sports facility in the hustle and bustle of City life.
includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Sports facilities -- Designs and plans